Infiltration Model of Mediterranean Soil with Clay Texture - Sitti Nur Faridah; Mahmud Achmad; Tisha Aditya Jamaluddin; Jusmira Jusmira (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Infiltration plays an essential role in increasing the soil water content as a part of the hydrological cycle. Infiltration affects surface runoff and soil conservation. It also determines the sustainability of the groundwater system. Heavy rain intensity exceeding the infiltration capacity will result in surface runoff, and excessive surface runoff will cause soil erosion.  This study aims to investigate the suitable infiltration rate model in the Mediterranean soil of clay textured with various soil conditions. Infiltration rate measurement employed a double-ring infiltrometer in soil without and with tillage. The applied infiltration rate model was an empirical model and the function of time, which includes the Kostiakov, Horton, and Philip Models. The results demonstrated that the Mediterranean soil infiltration rate with a clay texture was 0.91 cm/min and was relatively higher in the soil without tillage. The suitable infiltration rate model to be applied in soil conditions without and with tillage is the Kostiakov Model f = 0.700 t-0.25  and f = 0.682 t-0.22, respectively. The Kostiakov model is the most suitable infiltration rate model in Mediterranean textured clay, without tillage conditions, with a determination value of 0.988 and a deviation value of 0.005. Keywords: Horton model, Philip model, Infiltrometer; Kostiakov model, Tillage